2003
DOI: 10.1046/j.1365-2591.2003.00738.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro fracture resistance of root‐filled teeth using new‐generation dentine bonding adhesives

Abstract: In this laboratory study, the type of dentine bonding agents had no influence in the fracture resistance of teeth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 11 publications
2
25
0
1
Order By: Relevance
“…The clinical outcomes of direct resin composite restorations, which represent a less invasive approach to restoring endodontic posterior teeth, are variable in the literature, ranging from catastrophic to acceptable [4][5][6]. More recently, the insertion of fiber posts within direct composite restorations has been tested with the intention of providing increased fracture resistance [7][8][9]. Indeed, within the radicular dentin, the fiber post serves as a distributor of stresses and loads applied to the composite restoration [10], providing reinforcement even in the presence of sufficient residual coronal dentin [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The clinical outcomes of direct resin composite restorations, which represent a less invasive approach to restoring endodontic posterior teeth, are variable in the literature, ranging from catastrophic to acceptable [4][5][6]. More recently, the insertion of fiber posts within direct composite restorations has been tested with the intention of providing increased fracture resistance [7][8][9]. Indeed, within the radicular dentin, the fiber post serves as a distributor of stresses and loads applied to the composite restoration [10], providing reinforcement even in the presence of sufficient residual coronal dentin [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The embedding material should ideally simulate the capacity of bone to absorb masticatory load and therefore withstand the load applied in mechanical testing. However there is no consensus on the material that should be used and it varies greatly amongst studies: acrylic resin 19,22,30 or polystyrene resin 20,27 and die stone. 21,31 In the present study, an oblique load (458 to the long axis of the tooth) was applied to the occlusal incline of the buccal cusp using a rounded loading tip, which contacted the enamel surface away from the restoration margin.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, the direction of the applied load has included axial loading on both buccal and palatal cusps 16,17,32 or at 308 to the vertical on the buccal cusp incline, 27 or at the tooth-restoration interface. 15,18,22 Cavity preparations: Since the early work of Vale, 33 numerous authors have documented the weakening effect of cavity preparations on tooth strength and fracture resistance, although relatively few have investigated the effect of endodontic procedures. Reeh et al using non-destructive strain measurements, reported that endodontic access had little effect (5%) on cuspal stiffness compared with an MOD cavity preparation (63% reduction relative to intact teeth).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be related to the phenomenon of delayed strength development of MTA, which occurs after 24 h of setting 33) . A survey of published literature showed that the reinforcing effect of AH Plus root canal sealer on fracture resistance has already been evaluated in numerous studies 5,27,34,35) . In the present study, no differences in fracture strength were found among roots fi lled with AH Plus, iRoot SP, and MTA Fillapex.…”
Section: Effect Of Root Canal Sealers On Fracture Resistance Of Rootfmentioning
confidence: 99%